The Advance Care Compass- A New Mechanics for Digitally Transforming Advance Directives - Nikola Biller-Andorno; Armin Biller (Frontiers Media S.A., 2021)
Advance directives allow people to declare their treatment preferences for a potential future state of incompetency. Covid-19, with its high numbers of quickly deteriorating patients requiring intensive care, has acutely demonstrated how helpful it would be for clinicians to have reliable, readily available, up-to-date information at hand to be able to act in accordance with what the individual patient would have wanted. Yet for the past few decades advance directives have fallen short of their potential, for various reasons. At worst, advance directives are perceived as unwieldy legal documents that put excessive demands on patients without providing useful guidance for better care. Recent efforts such as advance care planning have tried to remedy some of these shortcomings but have so far met with limited success. We suggest a new concept-the Advance Care Compass-that harnesses the potential of digitalization in healthcare to overcome many of difficulties encountered so far.